Cfd Simulation Study of The Novel Multistage Inlet Gasifier For Enhancement of Syngas Production - Rosli, Muhammad Irfan; Samiran, Nor Afzanizam (Progress in Engineering Application and Technology, 2022)
Economically, fossil fuels remain the main source of energy despite their high emissions of greenhouse gases. However, biomass, a renewable fuel with CO2 neutrality, has experienced widespread attention as a potential contributor to the sustainable development of the energy sector. Gasification is an important thermochemical process that converts biomass feedstock into H2-rich combustible gases known as syngas. Its main product (syngas) can be used as fuel in various conversion technologies to produce different products, including electricity and chemicals. This research study focuses particularly on biomass gasification that is a promising technology to achieve high-quality syngas in the presence of one or more gasification agents. To accomplish this aim, a single-stage and two-stage downdraft reactor are analysed in this study using an equilibrium model with non-premixed combustion in the ANSYS Fluent. This study shows that the CFD model simulated values of outlet gas composition was in good agreement and was validated with the Paul1 model prediction and experimental data2. The highest temperature inside the gasifier for a single stage model is found in the oxidation zone, where the air is supplied. The temperature in the drying zone is less than 460K, in the pyrolysis zone is between 470 and 455K, in the oxidation zone is between 470 and 490K, and in the reduction zone is between 480 and 485K. The highest temperature inside the gasifier for a double stage model is found in the oxidation zone, where the air is supplied. The temperature in the drying zone is less than 470K, in the pyrolysis zone is between 470 and 480K, in the oxidation zone is between 470 and 520K, and in the reduction zone is between 480 and 485K. It is observe that the CO and H2 concentrations are higher in the pyrolysis zone for single and double stage as the volatile matter turn to gases phase due devolatilization process. Then for CH4 mole fraction, the single stage was 0.06% while the double stage was 0.03%.3 reported CH4 values similar to those found in this study. It is demonstrated the advantages of the double stage by supply air in gasification experiments in a downdraft gasifier.